Method for solidifying heavy metals by steam heat-enhanced silicon-aluminum minerals

By using technical means such as steam thermal curing and ion exchange in silicon and aluminum minerals, the stable curing problem of UO2+ in water bodies is solved, and the heavy metal curing effect with high stability and low leachate is achieved, avoiding secondary pollution.

CN119560204APending Publication Date: 2025-03-04GUANGZHOU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411813768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively stabilize UO2+ in cured water, and its stability after curing is questionable and it is prone to secondary pollution.

Method used

By putting silicon-aluminum minerals into uranium-containing wastewater, adjusting the pH so that they fully adsorb uranium ions, and then performing steam thermal curing treatment, the heavy metals are further fixed by ion exchange and unit cell polymerization to achieve stable curing.

Benefits of technology

It significantly improves the curing stability of silicon-aluminum minerals to heavy metals, reduces the leaching rate of heavy metals, avoids secondary pollution, and has a simple process flow and easy to control reaction conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560204A_ABST
    Figure CN119560204A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and particularly relates to a method for solidifying heavy metals by steam heat enhanced silicon-aluminum minerals. The method comprises the following steps: uniformly mixing silicon-aluminum minerals with uranium-containing wastewater, adjusting the pH value, combining uranium ions with the silicon-aluminum minerals through ion exchange action and surface adsorption action, carrying out maintenance treatment on a precipitate obtained by a mixed reaction by using steam heat, and strengthening the solidification effect of the silicon-aluminum minerals on heavy metal uranium, uranium is combined with a polymer three-dimensional network of the silicon-aluminum minerals, and part of uranium enters a polymer structure by replacing the positions of silicon atoms or aluminum atoms in aluminosilicate and is gradually stabilized in a polymer of bentonite of the silicon-aluminum minerals, so that the stability of the silicon-aluminum minerals for solidifying heavy metals is improved, and the leaching rate of the heavy metals is reduced. Therefore, the method provided by the invention can strengthen the effect of solidifying the heavy metals by the silicon-aluminum minerals and reduce the leaching rate of the heavy metals, and has the advantages of simple process flow, easy control of reaction conditions, strong operability and important practical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a method for steam thermally strengthening silicon-aluminum minerals to solidify heavy metals. Background Art

[0002] Uranium (U(VI)) is a very important natural radioactive heavy metal element, mainly used in the production and manufacture of nuclear industry raw materials. In nature, the abundance of uranium in the earth's crust is about 3×10 -3 g / kg, mainly in the form of +4 and +6 valence states in uranium-containing ores. With the gradual rise of sandstone uranium mining, a large amount of uranium-containing wastewater is produced during uranium mining, which mainly comes from well washing wastewater, waste drilling fluid, leaching tail liquid, and ion exchange tail liquid.

[0003] Uranium and its compounds are radioactive and heavy metal toxic. Long-term exposure can easily cause cancer in cells and tissues in the human body. Moreover, uranium will produce radon and radium during its decay. Radium is extremely radioactive and can instantly cause irreversible damage to the nervous system, blood circulation system and endocrine system. Therefore, achieving long-term stable solidification of U(VI), clarifying its principles and causes, and studying the stability mechanism of fixed U(VI) are of great practical significance for the treatment of uranium-containing wastewater.

[0004] At present, the focus at home and abroad is mainly on the use of adsorption, ion exchange, chemical precipitation, electrodeposition, membrane separation and other methods to remove UO2 from water. 2+ Among them, the adsorption method has the advantages of low cost, simple use, wide application range, high efficiency and feasibility, and is one of the important methods for treating uranium-containing wastewater. The main strategy of the adsorption method is to use adsorbents and adjust process parameters to achieve efficient UO2 2+ Removal rate, remove UO2 which is easy to migrate in water 2+ Transferred to an inert solid phase to solidify it, slowing down its migration activity in the environment. 2+ The stability of UO2 after transfer to the solid phase is questionable and has received little attention. 2+ The stabilization and solidification strategy of heavy metals in the solid phase will be an effective way to avoid their environmental pollution risks. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention proposes a method for steam-heat-enhanced silica-alumina mineral solidification of heavy metals. The method uses steam heat to cure the silica-alumina mineral that adsorbs uranium ions, so that the silica-alumina mineral further fixes the heavy metals through ion exchange and unit cell polymerization, thereby achieving a stable solidification effect of the heavy metal ions, and ultimately solving the problem of secondary pollution caused by re-leaching of heavy metals after fixation, thereby realizing the stabilization and solidification of uranium ions in wastewater.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The present invention provides a method for steam thermally strengthening silica-alumina minerals to solidify heavy metals, which specifically comprises: adding silica-alumina minerals into uranium-containing wastewater, adjusting the pH so that the silica-alumina minerals can fully adsorb uranium ions, and then performing steam thermal curing treatment on the mixture, thereby achieving the purpose of strengthening the silica-alumina minerals to solidify heavy metals.

[0008] The method of the present invention can enhance the effect of silicon-aluminum minerals in solidifying heavy metals, improve the stability of silicon-aluminum minerals in solidifying heavy metals, and reduce the leaching rate of heavy metals. The process flow is simple, the reaction conditions are easy to control, the operability is strong, and the method has important practical application prospects.

[0009] Preferably, the pH is adjusted to 3-9.

[0010] Preferably, the molar ratio of silicon to aluminum elements in the silicon-aluminum mineral is (3-5):1.

[0011] Preferably, the steam heat curing treatment is carried out at a temperature of 25-200°C and for a time of 20-30 hours.

[0012] Preferably, the process of allowing the silicon-aluminum mineral to fully adsorb uranium ions is carried out under oscillation conditions, and the adsorption time is 1-6 hours. Further, the process of allowing the silicon-aluminum mineral to fully adsorb uranium ions is carried out in an oscillator.

[0013] Preferably, the silica-alumina mineral comprises bentonite.

[0014] Preferably, the pH regulator is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid, lime, limestone, dolomite, sodium hydroxide, and sodium carbonate. Further, the pH regulator is at least one of nitric acid and sodium hydroxide.

[0015] Preferably, the concentration of the uranium-containing wastewater is 5-100 mg / L, and the dosage of the silicon-aluminum mineral is 5-20 g / L.

[0016] Preferably, the steam heat curing treatment is carried out in a polytetrafluoroethylene reactor, with an electric constant temperature drying oven providing the heat source.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The invention discloses a method for steam-heat-enhanced silica-alumina mineral solidification of heavy metals. The silica-alumina mineral is first mixed with uranium-containing wastewater and the pH is adjusted so that uranium ions are combined with the silica-alumina mineral through ion exchange and surface adsorption, and then the precipitate obtained by the mixed reaction is cured by steam heat to strengthen the solidification effect of the silica-alumina mineral on heavy metal uranium. In the steam-heat-enhanced process, uranium is combined with the polymer three-dimensional network of the silica-alumina mineral, and part of the uranium enters the polymer structure by replacing the position of silicon atoms or aluminum atoms in the silicate, and is gradually stabilized in the polymer of the silica-alumina mineral bentonite, thereby improving the stability of the silica-alumina mineral solidification of heavy metals and reducing the leaching rate of heavy metals. It can be seen that the method of the present invention realizes the stable solidification effect of the silica-alumina mineral on uranium ions through ion exchange, participation in polymerization reaction and three-dimensional network inclusion, so that the leaching rate is as low as 15.2%. In addition, the method of the present invention has a simple process flow, easy-to-control reaction conditions, strong operability, and has important practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a line graph of temperature-uranium ion leaching efficiency of uranium ion fixation by hydrothermal method of silica-alumina mineral at different temperatures;

[0020] Figure 2 The temperature-uranium ion leaching efficiency line graph of the steam thermal enhancement of uranium ion fixation in silica-alumina minerals at different temperatures;

[0021] Figure 3 It is a line graph of pH-uranium ion leaching efficiency of steam thermal enhancement for fixed uranium ions when the silicon-aluminum molar ratio is 3.85:(0-4);

[0022] Figure 4 This is a line graph of pH-uranium ion leaching efficiency for steam thermal enhancement of uranium ion fixation when the silicon-aluminum molar ratio is (0-8):1. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0024] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0025] In the following examples, the silica-alumina mineral used is bentonite, the uranium salt is uranyl nitrate hexahydrate, the uranium-containing wastewater is a 10 mg / L uranyl ion solution prepared in the laboratory, and the leaching agent is a desorption buffer solution with a pH value of 2.88 prepared by using acetic acid solution and sodium acetate solution.

[0026] Example 1: A method for steam-heat-enhanced solidification of heavy metals by silicon-aluminum minerals

[0027] Bentonite was added into uranium-containing wastewater, wherein the amount of bentonite added was 10 g / L, the initial concentration of uranium-containing wastewater (i.e., uranyl ion solution) was 10 mg / L, the pH value of the solution was controlled to be 3-9, and after being placed in an oscillator for reaction for 2 hours, it was transferred to a polytetrafluoroethylene reactor, and an electric constant temperature drying oven was used to provide a heat source. The water heating temperature was set to 25°C, 100°C, 150°C, and 200°C, respectively. After reacting for 24 hours, it was cooled to room temperature and centrifuged to collect 5 mL of the suspension after the reaction, filtered with a 0.45 μm microporous filter membrane, and the uranium ion concentration was analyzed by a micro-uranium meter (WGJ-Ⅲ) to obtain C t ; The separated residue was collected, washed and dried with deionized water, and dried to constant weight. The obtained constant weight solid was put into the leaching agent at room temperature at a liquid-to-solid ratio of 10:1 (L / kg), and placed on a tumbling oscillator (30r / min) for 18h before sampling. The suspension was filtered through a 0.45μm microporous membrane to obtain a filtrate, and then a micro-uranium meter (WGJ-Ⅲ) was used to analyze the concentration of residual uranium ions to obtain C d The uranium leaching rate is calculated based on the amount of uranium contained in the uranium solid body and the amount of uranium contained in the solution after leaching. The calculation formula is as follows:

[0028]

[0029] Where, D: desorption rate of U(VI);

[0030] C d : Desorbed U(VI) concentration in solution (mg / L);

[0031] V d : Volume of desorbent solution involved in the reaction (L);

[0032] C0: uranium content in the solution before adsorption (mg / L);

[0033] C t : The content of U(VI) in the reaction solution at t(min) (mg / L);

[0034] V0: volume of solution for initial adsorption reaction (mL).

[0035] like Figure 1As shown in the figure, when the pH value is 5, the uranium leaching rates are 37.07%, 26.48%, 23.03% and 21.53% under the hydrothermal conditions of 25℃, 100℃, 150℃ and 200℃ respectively. Under the hydrothermal conditions of 200℃, when the pH values ​​are 3, 5, 7 and 9 respectively, the uranium leaching rates are 29.21%, 21.53%, 22.66% and 38.47% respectively.

[0036] Example 2: A method for steam-heat-enhanced solidification of heavy metals by silicon-aluminum minerals

[0037] Bentonite was added into uranium-containing wastewater, wherein the dosage of bentonite was 10 g / L, the initial concentration of uranium-containing wastewater (i.e., uranyl ion solution) was 10 mg / L, the pH value of the solution was controlled at 3-9, and after being placed in an oscillator for reaction for 2 hours, it was centrifuged and 5 mL of the suspension after the reaction was collected and filtered with a 0.45 μm microporous filter membrane. The uranium ion concentration was analyzed by a microuranium meter (WGJ-Ⅲ) to obtain C1. The solid precipitate was collected and placed in a polytetrafluoroethylene reactor. An electric constant temperature drying oven was used as a heat source. The temperature was controlled at 25°C, 100°C, 150°C, and 200°C by water insulation heating. After reacting for 24 hours, the temperature was lowered to room temperature. The solid in the reactor was collected. The obtained constant weight solid was put into the leaching agent at room temperature at a liquid-solid ratio of 10:1 (L / kg). The solid was placed on a tumbling oscillator (30 r / min) for 18 hours and then sampled. The suspension was filtered through a 0.45 μm microporous membrane to obtain a filtrate. The concentration of residual uranium ions was analyzed using a microuranium meter (WGJ-Ⅲ) to obtain C d The uranium leaching rate is calculated based on the amount of uranium contained in the uranium solid body and the amount of uranium contained in the solution after leaching. The calculation formula is as follows:

[0038]

[0039] Where D: desorption rate of U(VI);

[0040] C d : Desorbed U(VI) concentration in solution (mg / L);

[0041] V d : Volume of desorbent solution involved in the reaction (L);

[0042] C0: uranium content in the solution before adsorption (mg / L);

[0043] C1: the content of U(VI) in the solution after the adsorption reaction is completed (mg / L);

[0044] V0: volume of solution for initial adsorption reaction (mL).

[0045] like Figure 2As shown, when the temperature is 25°C (equivalent to the control without steam heat treatment), the uranium leaching rates are 44.93%, 37.07%, 42.20% and 47.5% when the pH values ​​are 3, 5, 7 and 9 respectively; under the condition of steam heat curing at 200°C, the uranium leaching rates are 21.14%, 15.20%, 20.59% and 20.96% when the pH values ​​are 3, 5, 7 and 9 respectively; when the pH value is 5, the uranium leaching rates are 37.07%, 26.86%, 17.33% and 15.20% when the temperatures are 25°C, 100°C, 150°C and 200°C respectively.

[0046] Example 3: A method for steam-heat-enhanced solidification of heavy metals by silicon-aluminum minerals

[0047] Bentonite was added into uranium-containing wastewater, wherein the amount of bentonite added was 10 g / L, and the molar ratio of silicon and aluminum elements (Si / Al) in the bentonite was 3.85:0, 3.85:0.5, 3.85:1, 3.85:2, and 3.85:4, respectively. The initial concentration of uranium-containing wastewater (i.e., uranyl ion solution) was 10 mg / L, and the pH value of the solution was controlled to be 3-9. After being placed in an oscillator for reaction for 2 hours, the solution was transferred to a polytetrafluoroethylene reactor, and an electric constant temperature drying oven was used to provide a heat source. The water heating temperature was set to 200°C. After reacting for 24 hours, the solution was cooled to room temperature, centrifuged, and 5 mL of the suspension after the reaction was collected and filtered with a 0.45 μm microporous filter membrane. The uranium ion concentration was analyzed by a micro-uranium meter (WGJ-Ⅲ), and C t ; The separated residue was collected, washed and dried with deionized water, and dried to constant weight. The obtained constant weight solid was put into the leaching agent at room temperature at a liquid-to-solid ratio of 10:1 (L / kg), and placed on a tumbling oscillator (30r / min) for 18h before sampling. The suspension was filtered through a 0.45μm microporous membrane to obtain a filtrate, and then a micro-uranium meter (WGJ-Ⅲ) was used to analyze the concentration of residual uranium ions to obtain C d The uranium leaching rate is calculated based on the amount of uranium contained in the uranium solid body and the amount of uranium contained in the solution after leaching. The calculation formula is as shown in formula (1).

[0048] like Figure 3 As shown, under the solidification condition of 200°C, when the pH value is 5, the molar ratios of silicon and aluminum are 3.85:0, 3.85:0.5, 3.85:1, 3.85:2, and 3.85:4, respectively, the uranium leaching rates are 30.02%, 29.42%, 14.50%, 16.52%, and 22.36%, respectively; under the condition that the molar ratio of silicon and aluminum is 3.85:1, when the pH values ​​are 3, 5, 7, and 9, respectively, the uranium leaching rates are 22.49%, 14.50%, 17.29%, and 19.32%, respectively.

[0049] Example 4: A method for steam-heat-enhanced solidification of heavy metals by silicon-aluminum minerals

[0050] Bentonite was added into uranium-containing wastewater, wherein the amount of bentonite added was 10 g / L, and the molar ratio of silicon and aluminum elements (Si / Al) in the bentonite was 0:1, 2:1, 3.85:1, 6:1, and 8:1, respectively. The initial concentration of uranium-containing wastewater (i.e., uranyl ion solution) was 10 mg / L, and the pH value of the solution was controlled to be 3-9. After being placed in an oscillator for reaction for 2 hours, the solution was transferred to a polytetrafluoroethylene reactor, and an electric constant temperature drying oven was used to provide a heat source. The water heating temperature was set to 200°C. After reacting for 24 hours, the solution was cooled to room temperature and centrifuged. 5 mL of the suspension after the reaction was collected and filtered with a 0.45 μm microporous filter membrane. The uranium ion concentration was analyzed by a micro-uranium meter (WGJ-Ⅲ), and C t ; The separated residue was collected, washed and dried with deionized water, and dried to constant weight. The obtained constant weight solid was put into the leaching agent at room temperature at a liquid-to-solid ratio of 10:1 (L / kg), and placed on a tumbling oscillator (30r / min) for 18h before sampling. The suspension was filtered through a 0.45μm microporous membrane to obtain a filtrate, and then a micro-uranium meter (WGJ-Ⅲ) was used to analyze the concentration of residual uranium ions to obtain C d The uranium leaching rate is calculated based on the amount of uranium contained in the uranium solid body and the amount of uranium contained in the solution after leaching. The calculation formula is as shown in formula (1).

[0051] like Figure 4 As shown, under the solidification condition of 200°C, when the pH value is 5, the molar ratios of silicon and aluminum are 0:1, 2:1, 3.85:1, 6:1, and 8:1, respectively, the uranium leaching rates are 53.53%, 18.86%, 15.76%, 19.15%, and 27.92%, respectively; under the condition that the molar ratio of silicon and aluminum is 3.85:1, when the pH values ​​are 3, 5, 7, and 9, respectively, the uranium leaching rates are 23.85%, 15.76%, 18.43%, and 19.62%, respectively.

[0052] It can be seen from the above examples that after the silicon-aluminum mineral adsorbs uranium at room temperature to obtain a uranium-containing solidified material, it is cured by steam heat, so that the silicon-aluminum elements in the silicon-aluminum mineral interact with the heavy metal uranium, and the uranium is further fixed by ion exchange and three-dimensional network polymerization structure (cell polymerization), thereby achieving a stable solidification effect of the heavy metal uranium. The method of solidifying uranium with silicon-aluminum minerals by steam heat enhancement of the present invention has a low leaching rate, greatly improves the effect of silicon-aluminum minerals solidifying heavy metals, and has important practical application prospects.

[0053] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for steam thermally strengthening the solidification of heavy metals by silicon-aluminum minerals, characterized in that: Silica-alumina minerals are put into uranium-containing wastewater, and the pH is adjusted to allow the silica-alumina minerals to fully adsorb uranium ions. The mixture is then subjected to steam thermal curing treatment to achieve the purpose of strengthening the silica-alumina minerals to solidify heavy metals.

2. The method for steam thermally strengthening the solidification of heavy metals by silicon-aluminum minerals according to claim 1, characterized in that: Adjust pH to 3-9.

3. The method for steam thermal enhancement of silicon-aluminum mineral solidification of heavy metals according to claim 1, characterized in that: The molar ratio of silicon to aluminum elements in the silicon-aluminum mineral is (3-5):

1.

4. The method for steam thermally strengthening the solidification of heavy metals by silicon-aluminum minerals according to claim 1, characterized in that: The temperature of the steam heat curing treatment is 25-200° C. and the time is 20-30 hours.

5. The method for steam thermal enhancement of silicon-aluminum mineral solidification of heavy metals according to claim 1, characterized in that: The silica-alumina mineral is allowed to fully adsorb uranium ions under oscillating conditions, and the adsorption time is 1-6 hours.

6. The method for steam thermal enhancement of silicon-aluminum mineral solidification of heavy metals according to claim 1, characterized in that: The silica-alumina mineral includes bentonite.

7. The method for steam thermally strengthening the solidification of heavy metals by silicon-aluminum minerals according to claim 1, characterized in that: The pH regulator is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid, lime, limestone, dolomite, sodium hydroxide and sodium carbonate.

8. The method for steam thermal enhancement of silicon-aluminum mineral solidification of heavy metals according to claim 1, characterized in that: The concentration of the uranium-containing wastewater is 5-100 mg / L, and the dosage of the silicon-aluminum mineral is 5-20 g / L.

9. The method for steam thermal enhancement of silicon-aluminum mineral solidification of heavy metals according to claim 1, characterized in that: The steam heat curing treatment is carried out in a polytetrafluoroethylene reactor, and the heat source is provided by an electric constant temperature drying oven.